The Role of Collateral Quality in the Resolution Process of Non- Performing Financing at Bank NTB Syariah - Husni, Muslihun, Dahlia Bonang (Journal of Educational Studies, 2025)
This study analyzes the role of collateral quality in the settlement of non-performing financing at Bank NTB Syariah. The study is motivated by the importance of collateral as a risk mitigation instrument in Islamic banking, which plays a crucial role in determining the success of financing recovery. Using a qualitative case study approach, data were collected through interviews, observation, and documentation involving financing officers and risk management staff and were analyzed through data reduction, data presentation, and conclusion drawing techniques. The findings show that collateral quality significantly influences the effectiveness of non-performing financing settlement. High-quality collateral characterized by clear legal certainty, complete documentation, stable value, and high liquidity can accelerate the settlement process and reduce losses, while weak collateral tends to slow down liquidation and increase financing risk. Several obstacles were identified, including incomplete legal documents, ownership disputes, declining asset values, low market demand for certain assets, and limited collateral appraisal capability. The bank addresses these issues through improved verification processes, inter-unit coordination, periodic valuation, prioritization of restructuring before collateral execution, and staff training. This study concludes that effective collateral quality management is essential to optimize non-performing financing settlement and maintain financing risk stability in Islamic banking.